Pengukuran dan Penilaian Status Gizi Anak Sekolah Dasar Negeri 100 Kendari Menggunakan Indeks Massa Tubuh Menurut Umur - Muchtar, Febriana; Rejeki, Sri; Batara, Sofrine Eunike; Shaleh, Rajuma; Rasni, Wa; Andri, Muh; Samiru, Ainun Jariah; Izmi, Nur (Jurnal Abdi Mas Adzkia, 2023)
The growth and development of school-age children are linked to their nutritional status. It is necessary to monitor the nutritional well-being of these children, as issues during this crucial period can have lasting effects on their future and impact the overall quality of human resources. This research was performed to measure and assess the nutritional status of elementary school children at State Elementary School 100 Kendari based on the Body Mass Index for Age (BMI/A). The participants were pre-adolescents aged between 10-12 years old at the fourth, fifth, and sixth grade totaling to 63 students. The anthropometric measurements of weight and height was used as the primary method for assessment. Nutritional status was determined through the BMI/A. The results indicate that in the fourth grade, 12 students (57%) were classified as underweight, 8 students (38%) as normal, and 1 student (5%) as overweight. Similarly, in the fifth grade, 10 students (48%) were under weight, 8 students (38%) were normal, and 3 students (14%) were overweight. In the sixth grade, 9 students (43%) were under weight, 9 students (43%) had a normal nutritional status, and 3 students (14%) were overweight. Regular monitoring of nutritional status is emphasized as a preventive measure against nutritional problems in school-age children.